2015
DOI: 10.4238/2015.december.14.17
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the relationship between slow acetylation of N-acetyl transferase 2 and the risk of bladder cancer

Abstract: ABSTRACT. The incidence of bladder cancer is closely associated with exposure to aromatic amines, that can cause cancer only after metabolic activation regulated by N-acetyl transferase 1 and 2 (NAT1 and NAT2). Many studies have indicated that slow acetylation of NAT2 increases the risk of bladder cancer. The major risk factor is tobacco smoke; however, some studies have failed to prove this. This study attempted to explore the correlation between NAT2 slow acetylation and bladder cancer risk through a meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Interestingly, a genetic predisposition to bladder cancer has been previously reported, involving genes that control carcinogen metabolism, such as N -acetyltransferase 2 ( NAT2 ). Moreover, genome-wide association studies (GWAS) have identified sequence variants that can increase susceptibility to the disease, with alterations in the urea transporter SLC14A1 gene being characteristic examples [5,14,15,16,17,18,19,20,21,22,23].…”
Section: Epidemiology—risk Factorsmentioning
confidence: 99%
“…Interestingly, a genetic predisposition to bladder cancer has been previously reported, involving genes that control carcinogen metabolism, such as N -acetyltransferase 2 ( NAT2 ). Moreover, genome-wide association studies (GWAS) have identified sequence variants that can increase susceptibility to the disease, with alterations in the urea transporter SLC14A1 gene being characteristic examples [5,14,15,16,17,18,19,20,21,22,23].…”
Section: Epidemiology—risk Factorsmentioning
confidence: 99%
“…A study in 2011 identified global histone H4K20 trimethylation that could predict cancer-specific survival in patients with muscle-invasive bladder cancer [28]. A meta-analysis published by An et al showed that merged odds ratio of the effect between slow acetylation and bladder cancer was 1.31 (95% confidence odds ratio interval = 1.11–1.55), illustrating that slow acetylation modestly increases the risk of bladder cancer [29]. Recently, Jia et al found that the acetylation status of KLF4 can decide the gene function as a tumor suppressor or oncogene in bladder cancer.…”
Section: Epigenetic Biomarkers In Bladder Cancermentioning
confidence: 99%
“…The influence of NAT2 genetic variability to the acetylation phenotype and, consequently, to the therapeutic outcomes of those drugs has been demonstrated for several disease models, including for tuberculosis and hypertension among others ( Possuelo et al, 2008 ; Teixeira et al, 2011 ; Spinasse et al, 2014 ). Moreover, NAT2 variability has been investigated as a possible risk factor for xenobiotic-related susceptibility to Alzheimer’s disease, schizophrenia, diabetes, cataract, and parkinsonism ( Bialecka et al, 2002 ; Agúndez et al, 2008 ; Luan et al, 2017 ), while it is also linked to urinary bladder and colorectal cancers ( García-Closas et al, 2005 ; An et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%